PENGARUH PENAMBAHAN BERBAGAI KADAR PISANG DAN UBI JALAR PADA PERTUMBUHAN KULTUR TIGA JENIS PHALAENOPSIS - Garvita, Raden Vitri; Handini, Elizabeth (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
The aim of the experiment was to determine the effect of organic materials on the growth of Phalaenopsis zebrina, P. Â javanica and P. Â fuscata explants without rootsÂ in Knudsonâs C medium with additional of coconut water. Â Observation were conducted for 10 months and the data were analyzed by ANOVA. The result showed that the survival ability of P. zebrina and P. javanica were only 3 months in KC medium with additional of coconut water (150 g/l), banana (50 g/l) and sweet potatoes (20 g/l), while P. fuscata grew further up to 10 months in all media. Additional of organic material: 150 g/l coconut water, 25 g/l banana and 15 g/l sweet potatoes in KC medium gave the best result on increasing the leaf and the shoot numbers, while additional of 150 g/l coconut water, 50 g/l banana and 20 g/l sweet potatoes to KC medium only increasing theÂ root number of P. fuscata.